Carbonaceous electrode materials for supercapacitor: Preparation and surface functionalization - Lv, Yaokang; Wang, Juncheng; Ji, Dingwei; Li, Jianhang; Zhao, Suaisuai; Zhao, Yingjian; Cai, Zhiwei; He, Xuehua; Sun, Xiaofang (Frontiers in Energy Research, 2023)
Supercapacitors played an important role in energy conversion and storage, their large power deliveries abilities, high stability and environmental friendliness characteristics draw tremendous attention in high-power applications such as public transit networks. Carbonaceous materials with unique surface and electrochemical properties were widely used in supercapacitors as electrode materials. This review focuses on the developments in supercapacitor electrodes made from carbonaceous materials recently, Their working principle and evaluation parameters were summarized briefly. The preparation methods and electrochemical properties of different carbonaceous materials were compared and classified. It was found that the surface situation (eg. porous structure, hydrophilic) of carbonaceous materials strongly affect the electrochemical performances of supercapacitor. So far, active carbons would be the most applicable carbonaceous electrode materials due to their extensive accessibility, inexpensiveness, good chemical stability and conductivity. But their energy densities still fall behind practical demands. Both theoretical calculations and experimental studies show that surface modification and doping of carbonaceous materials can not only optimize their pore size, structure, conductivity and surface properties, but also can introduce extra pseudocapacitance into these materials. Considering global environmental pollution and energy shortage problems nowadays, we sincerely suggested that future work should focus on domestic, medical and industrial wastes residues derived carbonaceous materials and scaled production process such as reactors and exhaust gas treatment.